The Woman in Haider Haider’s Novel Experience - فاضل ياسر; ميا فاخر; مروشية محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Haider Haider’s search for audacity and his ability to delve into the mysteries of the realm of femininity spoke of breaking into what we called the critical region. Then the research moved to clarify the nature of the presence of women and the aesthetics of that presence by talking about: The Rafidah woman who does not accept the mainstream and the traditional. - The woman searching for the self (the other or the man) in an unfamiliar narrative context that gives women a special kind of glamor and suspense. To reach the top of creative maturity; It is the state of identification that occurred between creativity and women, where women became a substitute for the homeland in the time of migrations and exile and the loss of the childhood bed. Then comes the conclusion to clarify the results of the research and show the importance of the presence of women in creativity, ancient and modern, and in the times to come.